Perceived Social Standing, Medication Nonadherence, and Systolic Blood Pressure in the Rural South. Issue 2 (3rd September 2015) - Cummings, Doyle M.; Wu, Jia‐Rong; Cene, Crystal; Halladay, Jacquie; Donahue, Katrina E.; Hinderliter, Alan; Miller, Cassandra; Garcia, Beverly; Penn, Dolly; Tillman, Jim; DeWalt, Darren
Abstract: Purpose: Little is known about how perceived social standing versus traditional socioeconomic characteristics influence medication adherence and blood pressure (BP) among African American and white patients with hypertension in the rural southeastern United States. Methods: Perceived social standing, socioeconomic characteristics, self‐reported antihypertensive medication adherence, and BP were measured at baseline in a cohort of rural African American and white patients (n = 495) with uncontrolled hypertension attending primary care practices. Multivariate models examined the relationship of perceived social standing and socioeconomic indicators with medication adherence and systolic BP. Findings: Medication nonadherence was reported by 40% of patients. Younger age [β = 0.20; P = .001], African American race [β = ‐0.30; P = .03], and lower perceived social standing [β = 0.08; P = .002] but not sex or traditional socioeconomic characteristics including education and household income, were significantly associated with lower medication adherence. Race‐specific analyses revealed that this pattern was limited to African Americans and not observed in whites. In stepwise modeling, older age [β = 0.57, P = .001], African American race [β = 4.4; P = .03], and lower medication adherence [β = ‐1.7, P = .01] but not gender, education, or household income, were significantly associated with higher systolic BP. Conclusions: Lower perceived social standing and age, but not traditional socioeconomic characteristics, were significantly associated with lower medication adherence in African Americans. Lower medication adherence was associated with higher systolic BP. These findings suggest the need for tailored, culturally relevant medication adherence interventions in rural communities.